Crime analysis in the Municipality Puconci with the use of crime mapping method - Eman, Katja; Hacin, Rok (Anali PAZU HD, 2022)
The aim of crime mapping is a synthesis of the findings of the analysis of the selected security problem and presentation of the findings on clear and transparent maps in order to establish facts and to find proper solutions. The purpose of this paper was to study the case of safety in the municipality of Puconci using the crime mapping method. The graphical presentation of the crime distribution on the territory of the municipality Puconci in the period 2008 - 2012 shows that majority of the crime cases were committed in the populated areas of local communities Zenkovci, Brezovci and Puconci; specifically in the villages Zenkovci, Beznovci, Brezovci, Gorica and Puconci where the crime hot spots and areas were identified. In the local community Mačkovci the analysed crime offences are the most scattered. The most common form of crime are crimes against property, where thefts are far most often, followed by offenses against public order and crimes against human rights and freedoms. This kind of security problems residents rather than with the presence and activity of the police (e.g. police patrols) can solve with increased self-protective behaviour. More attention and cooperation between competent services, such as police, social work centres and other agencies is required by criminal offenses against marriage, family and youth as they interfere with the basic cell of society, i.e., family, and often leave behind irreversible consequences. It can be concluded that the municipality Puconci is relatively safe municipality, with an average of 3-times lower crime rate compared to the national level. Quick response of the agencies, especially the police, and a good social network undoubtedly have a positive impact on the high level of security, in terms of both crime and road safety.
Keywords: Municipality Puconci; crime mapping; crime densit